Simulasi Sistem Keamanan Palang Pintu Kereta Api Menggunakan Mikrokontroler Arduino Uno - Naufal Cahyo Widodo; Andi Purwanto; Nadita Dwi Pramesti; Paul Manurung; Didik Aribowo (Jupiter: Publikasi Ilmu Keteknikan Industri, Teknik Elektro dan Informatika, 2024)
The railway doorstop system functions to increase the safety of road users and avoid accidents at crossings. This journal discusses the design and implementation of a train doorstop system using Arduino Uno with supporting components such as servo motors, LED lights, resistors and the HC-SR04 ultrasonic sensor. The simulation aims to automate the process of closing and opening gate latches based on the presence of trains, with results demonstrating the effectiveness of the system in improving safety at crossings.